Comparison of left atrial strain by feature-tracking cardiac magnetic resonance with speckle-tracking transthoracic echocardiography - Benjamin, Mina M.; Munir, Muhammad S.; Shah, Parth; Kinno, Menhel; Rabbat, Mark; Sanagala, Thriveni; Syed, Mushabbar A. (The international journal of cardiovascular imaging, 2022)
Left atrial (LA) strain is a novel non-invasive parameter for assessing LA hemodynamics and function. We sought to compare the intermodality differences between transthoracic echocardiography (TTE) and cardiac magnetic resonance (CMR) derived LA strain, as well as reproducibility of strain measurements. We evaluated 70 subjects (mean age 42.1 ± 17 years, 44% males) with no significant cardiovascular disease who underwent both CMR and TTE within 6 months of each other. LA strain measurements i.e. reservoir strain (ƐR), conduit strain (ƐCD), and contractile strain (ƐCT), were compared using speckle-tracking echocardiography (STE) and CMR feature tracking (CMR-FT). Correlation and systematic bias between modalities was evaluated using intraclass correlation coefficient (ICC) and proportional bias. TTE was performed before CMR with a median duration of 33 days (IQR 14–69 days). ICC for ƐR, ƐCT, ƐCD was 0.66 (95% CI 0.44–0.79), 0.63 (95% CI 0.4–0.77) and 0.56 (95% CI 0.3–0.73) respectively. There was evidence of systematic bias between modalities, on average LA volume was found to be 19% higher on CMR than TTE. Strain values were also higher by CMR-FT compared to STE with mean difference of 9.9 ± 12 (26.1%), 3.1 ± 5.5 (21.9%), 4.0 ± 9.9 (16.6%) for ƐR, ƐCT and ƐCD respectively. Regression showed proportional bias for both ƐR, and ƐCT (beta 0.76, 0.54 respectively; P < 0.0001). There were modest differences in intraobserver reproducibility between both modalities with better reproducibility for STE compared to CMR-FT. There was a modest intermodality correlation between STE and CMR-FT derived LA strain components. There were systematic differences and proportional bias in measurements between modalities. These differences should be considered when interpreting LA strain using either modality.